IMPLEMENTATION OF COOPERATIVE LEARNING MODELS EXAMPLE NOT EXAMPLE IMPROVE THE LANGUAGE SKILLS OF CHILDREN - Mar’atus Salamah (Publikasi Indonesia, 2023)
This research aims to improve language skills through the application of the cooperative learning model of the type example of non example of Group B in the town of Cirebon Annida Kindergarten. This event will also be based on research by a monotonous learning method resulted in a low-level language ability group B, as well as learning that only limited work on Worksheet a child (LKA). This type of research is the research action class according to Kurt Lewin. The subject in this study as many as 12 children. The object in this research is language skills through the application of cooperative learning model of the type example of non example. Method of data collection in this research are observation, interview, and documentation, while data analysis techniques using the technique of qualitative and quantitative descriptive analysis. Research results can be known from observation of developments in each cycle during the pre-cycle of 53.85%, on cycle 1 of 64.38% with an increase of 10.53% and on cycle 2 of 78.68% with an increase of 14.3%, thus percentage increase in language skills through the application of the cooperative learning model of the type example of non example of success indicators, namely reaching 75%. As for the success of these done with the steps as below: 1) gives a description of the steps the implementation of cooperative learning model of the type example of non example, 2) researchers increase the size of the image that will observe, 3 children) the teacher always provide motivation